Optimal Array Reconfiguration of a PV Power Plant for Frequency Regulation of Power Systems - He, Tingyi; Li, Shengnan; Chen, Yiping; Wu, Shuijun; Li, Chuangzhi (Frontiers in Energy Research, 2021)
This paper establishes a novel optimal array reconfiguration (OAR) of a PV power plant for secondary frequency control of automatic generation control (AGC). Compared with the existing studies, the proposed OAR can further take the AGC signal responding into account except the maximum power output, in which the battery energy storage system is used to balance the power deviation between the AGC signals and the PV power outputs. Based on these two conflicted objects, the OAR is formulated as a bi-objective optimization. To address this problem, the efficient non-dominated sorting genetic algorithm II (NSGA-II) is designed to rapidly obtain an optimal Pareto front due to its high optimization efficiency. The decision-making method called VIKOR is employed to determine the best compromise solution from the obtained Pareto front. To verify the effectiveness of the proposed bi-objective optimization of OAR, three case studies with fixed, step-increasing, and step-decreasing AGC signals are carried out on a 10×10 total-cross-tied PV arrays under partial shading conditions.